Chlorogenic Acid Supplementation Benefits Zebrafish Embryos Exposed to Auranofin - Jasper Z. S. Chiu; Isabella Hold; Trent A. C. Newman; Julia A. Horsfield; Arlene McDowell (Pharmaceutics, 2020)
Antioxidant supplementation may potentially be beneficial for embryonic development to reduce complications associated with increased levels of oxidative stress. Chlorogenic acid, one of the key polyphenolic antioxidants in S. oleraceus, was evaluated for potential protective effects during embryonic development of zebrafish exposed to the teratogen auranofin. Zebrafish embryos were transiently exposed to auranofin to induce developmental abnormalities. Phenotypic abnormalities were scored based on their severity at day 5 post-fertilization. The embryos supplemented with 250 µM chlorogenic acid showed a significantly lower score in phenotypic abnormalities compared to non-supplemented embryos after auranofin exposure. Therefore, supplementation with a low dose of chlorogenic acid showed a protective effect from auranofin-induced deformities and encouraged normal growth in zebrafish embryos. This study provides further support for the potential of using antioxidant supplementation during embryonic development for protection against malformation.